Diagnostics and therapy for children with Down’s Syndrome in the range of own research and literature review - Sadowska, Ludwika; Mysłek-Prucnal, Monika; Choińska, Anna Maria; Mazur, Artur (European Journal of Clinical and Experimental Medicine, 2009)
<span style="color: #010101; font-family: Lato, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Prevalence of Down's Sydrome (DS) among newborn's who were born alive is 1:600-700.lt is the ‘most frequent aberration chromosomes. Down's Syndrome is a syndrome resulted from incomplement embryogenesis from the presence of added autosomal chromosome 21 in kariotype .Genetical material overexpression results in metabolic disorders , tissue dysmorphism , numerous internal organ defects, phenotype typical traits with various grade of mental retardation. The current knowledge level on diagnostics and Down's Sydrome therapy based on own experience and literature was shown in this paper.